Targeting Fibrosis: From Molecular Mechanisms to Advanced Therapies - Xingpeng Di; Ya Li; Jingwen Wei; Tianyue Li; Banghua Liao (Advanced Science)
Abstract As the final stage of disease‐related tissue injury and repair, fibrosis is characterized by excessive accumulation of the extracellular matrix. Unrestricted accumulation of stromal cells and matrix during fibrosis impairs the structure and function of organs, ultimately leading to organ failure. The major etiology of fibrosis is an injury caused by genetic heterogeneity, trauma, virus infection, alcohol, mechanical stimuli, and drug. Persistent abnormal activation of “quiescent” fibroblasts that interact with or do not interact with the immune system via complicated signaling cascades, in which parenchymal cells are also triggered, is identified as the main mechanism involved in the initiation and progression of fibrosis. Although the mechanisms of fibrosis are still largely unknown, multiple therapeutic strategies targeting identified molecular mechanisms have greatly attenuated fibrotic lesions in clinical trials. In this review, the organ‐specific molecular mechanisms of fibrosis is systematically summarized, including cardiac fibrosis, hepatic fibrosis, renal fibrosis, and pulmonary fibrosis. Some important signaling pathways associated with fibrosis are also introduced. Finally, the current antifibrotic strategies based on therapeutic targets and clinical trials are discussed. A comprehensive interpretation of the current mechanisms and therapeutic strategies targeting fibrosis will provide the fundamental theoretical basis not only for fibrosis but also for the development of antifibrotic therapies.